It Takes a Village: Multimodality Imaging of Cardiac Amyloidosis - Jean Michel Saad; Ahmed Ibrahim Ahmed; Dixitha Anugula; Yushui Han; Moath Said Alfawara; Mouaz H. Al-Mallah (Methodist DeBakey Cardiovascular Journal)
Cardiac amyloidosis (CA) is the buildup and infiltration of amyloid plaque in cardiac muscle. An underdiagnosed form of restrictive cardiomyopathy, CA can rapidly progress into heart failure. CA is evaluated using a multimodality approach that includes echocardiography, cardiac magnetic imaging, and nuclear imaging. Echocardiography remains an essential first-line modality that raises suspicion for CA and establishes functional baselines. Cardiac magnetic imaging provides additional incremental value via high-resolution imaging, robust functional assessment, and superior tissue characterization, all of which enable a more comprehensive investigation of CA. Cardiac scintigraphy has eliminated the need for invasive diagnostic approaches and helps differentiate CA subtypes. Positron emission tomography is the first modality introducing targeted amyloid binding tracers that allow for precise burden quantification, early detection, and disease monitoring. In this review, we highlight the role of several cardiac imaging techniques in the evaluation of CA.